Implementation of Integrated Cambridge and 2013 Curriculum of English at Tazkia International Islam Boarding School Malang - Muhammad Victor Syafi'i (Language-Edu, 2019)
The curriculum is a system that has several components to achieve a goal. The curriculum acts as an energy component for education, energy that supports the success of the objectives of each component of education to achieve educational goals. Therefore curriculum development dynamically needs to be done to meet the demands and changes that occur in the community. Curriculum integration is an effort to develop a better curriculum, especially in English language. In this lesson, the Cambridge curriculum used a language skills approach. In the 2013 Curriculum, the approach applied was language competence which included grammatical competence, social competence, and communicative competence.The purpose of this study was to describe the results of the integration curriculum (Cambridge and 2013 curriculum) on English subject, while also explaining the process of implementing learning using Integrated Curriculum (Cambridge Curriculum and 2013 Curriculum) on English subject. It also describe the strengths and weaknesses of the implementation of the integration curriculum (Cambridge curriculum and 2013 curriculum) on English subjects and can describe the constraints of implementing the English Integrated Curriculum (Cambridge and Curriculum 2013) on VIII grade at TAZKIA international Islamic boarding school Malang.This research is a qualitative research. It was conducted on VIII grade students at TAZKIA international Islamic boarding school Malang. The subjects of this study were the head of the madrasa, the deputy head of the madrasah curriculum section, the English teacher and students. The research tools used were interview guides, documentation sheets and observations, and student questionnaires. The data obtained was analyzed descriptively.Integration curriculum results, namely, in the process of integrating the Cambridge curriculum and the 2013 curriculum, there are adaptation and adoption processes. The adoption process is carried out on material content that is not in the 2013 curriculum but feels important in the Cambridge curriculum. The process of implementing learning by using Integration curriculum has 3 stages, namely learning planning, learning implementation, and learning assessment. Of the three stages, the English teacher of TAZKIA international Islamic boarding school Malang has carried out the process of implementing learning by using the Integration curriculum very well. The advantages of implementing integrated curriculum at TAZKIA international Islamic boarding school Malang are that the English language and reasoning skills of students increase.